(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines how empowering young people correlates with their choices for sustainable living, focusing particularly on the impact of marketing strategies. The researcher employed judgmental sampling, a non-probability method, and gathered data through a questionnaire from individuals aged 16-35, representing diverse demographics and educational backgrounds. The research evaluates participants’ awareness of sustainable practices, their involvement in ecofriendly activities, and their views on how marketing influences the promotion of environmentally conscious lifestyles.